2017
DOI: 10.3389/fpsyg.2017.01480
|View full text |Cite
|
Sign up to set email alerts
|

Can We Retrieve the Information Which Was Intentionally Forgotten? Electrophysiological Correlates of Strategic Retrieval in Directed Forgetting

Abstract: Retrieval inhibition hypothesis of directed forgetting effects assumed TBF (to-be-forgotten) items were not retrieved intentionally, while selective rehearsal hypothesis assumed the memory representation of retrieved TBF (to-be-forgotten) items was weaker than TBR (to-be-remembered) items. Previous studies indicated that directed forgetting effects of item-cueing method resulted from selective rehearsal at encoding, but the mechanism of retrieval inhibition that affected directed forgetting of TBF (to-be-forgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Retrieval orientations have been linked to the cognitive control of episodic retrieval via the presence of stimulus-locked orientation effects in conjunction with neural evidence of ‘strategic retrieval’ ( Herron and Rugg, 2003 , Dzulkifli and Wilding, 2005 , Dzulkiflil et al., 2006 , Morcom and Rugg, 2012 , Rosburg et al., 2013 , Mao et al., 2017 ). Strategic retrieval refers to the controlled recollection of task-relevant contextual details alongside a reduction in the recollection of less-relevant memories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieval orientations have been linked to the cognitive control of episodic retrieval via the presence of stimulus-locked orientation effects in conjunction with neural evidence of ‘strategic retrieval’ ( Herron and Rugg, 2003 , Dzulkifli and Wilding, 2005 , Dzulkiflil et al., 2006 , Morcom and Rugg, 2012 , Rosburg et al., 2013 , Mao et al., 2017 ). Strategic retrieval refers to the controlled recollection of task-relevant contextual details alongside a reduction in the recollection of less-relevant memories.…”
Section: Introductionmentioning
confidence: 99%
“…Neural evidence for strategic retrieval takes the form of significantly larger neural correlates of recollection for targets than for nontargets, these being the ‘left parietal old/new effect’ in ERP studies (i.e. a positive-going shift at left parietal electrode sites for recollected items; ( Herron and Rugg, 2003 , Dzulkifli and Wilding, 2005 , Rosburg et al., 2013 , Mao et al., 2017 )) and left angular gyrus activation in the fMRI parallel ( Morcom and Rugg, 2012 ). The fact that all of these studies reported neural correlates of strategic retrieval in conjunction with stimulus-locked neural correlates of retrieval orientation indicates that strategic retrieval may be enabled by the maintenance of target-centric retrieval orientations which facilitate the recollection of target memories at the expense of nontarget memories.…”
Section: Introductionmentioning
confidence: 99%
“…Second, pre-stimulus ERPs also differ according to target designation 11, 27 . Third, ERP measures of recollection associated with nontargets are significantly smaller than those associated with targets, this being the parietal old/new effect in ERP studies 12, 22, 35, 36 and activation in angular gyrus in their fMRI counterpart 18 . This third aspect is termed ‘strategic retrieval’ and there was evidence for this in control participants here, with target ERPs eliciting greater positivity than both nontargets and new items .…”
Section: Discussionmentioning
confidence: 95%
“…‘Strategic retrieval’ refers to the prioritised retrieval of goal-specific contextual information, and manifests as larger recollection effects for targets than for nontargets. The ERP correlate of recollection is enhanced positivity at parietal electrode sites between 500–800ms, and this is often significantly larger for targets than for nontargets 12, 22, 35, 36 . Elward et al 33 found that participants with high working memory capacity (measured using O-span performance) showed ERP evidence of strategic retrieval, but that this was eliminated following the Stroop task.…”
Section: Introductionmentioning
confidence: 99%
“…The present study does not involve a discussion of emotions and personality traits. Because Mao et al (2017) found that participants also experienced DF of specific nouns under a self-referential condition [8, 24], we chose specific nouns that were related closely to daily life as materials.…”
Section: Introductionmentioning
confidence: 99%